Effect of Isokinetic Training on Quadriceps Muscle Strength in Osteoarthritis of Knee - NARESH, BHASKAR RAJ (2017)
Knee Osteoarthritis is twice as common as hand or hip osteoarthritis with an incidence of 240 out of 100,000 population/ year affecting about 15% of the human population globally. The aim of the present study was to investigate the role of Isokinetic Training and EMG biofeedback training in improving strength of quadriceps femoris in participants with Osteoarthritis of knee. Fifty four participants in the age range of 50-63 years with knee Osteoarthritis of Grade II and III (Kellgren-Lawrence criteria) severity were recruited from the Department of Orthopedics, Hospital Universiti Sains Malaysia. The strength of quadriceps femoris was assessed at baseline employing the isokinetic device BIODEX 4 System Pro. The participants were randomly categorized into three groups (Gr.) Viz. Gr. A (conventional physiotherapy), Gr. B (isokinetic training) , Gr. C (EMG Biofeedback) and thus each group consisted of 18 participants. All the interventions were imparted for 25 - 30 minutes per session; 2 sessions per week for 10 weeks (20 sessions). Mid term evaluation was done at the 5th week, post intervetnion assessment at the end of 10 the week of intervention and follow up at 14th and 18th week. Quadriceps muscle strength improved in all the intervention groups. Two-way repeated measure of ANOVA revealed that, the average peak torque of quadriceps femoris at 180 degree/ second was significantly higher (p<0.05) in participants of the isokinetic training group compared with that of the participants of the conventional physiotherapy and EMG Biofeedback group. Isokinetic Training was effective in enhancing the muscle-strength in participants suffering from Osteoarthritis of knee.